Analisis Peran APIP dalam Meningkatkan Pengendalian Intern pada Perangkat Daerah di Lingkungan Pemerintah Kota Pekanbaru - Nur Agia, Lintang; Ramadhani, Hikmah; Hayati, Restu; Susanti, Efi (Akuntansi & Ekonomika, 2025)
This study aims to analyze the role of the Government Internal Supervisory Apparatus (Aparat Pengawasan Intern Pemerintah or APIP) in strengthening internal control systems within regional government agencies in Pekanbaru City. A descriptive qualitative approach was employed using data source triangulation, integrating survey results, in-depth interviews, and document analysis. A total of 12 key informants were purposively selected, consisting of auditors and internal control officers with direct experience in compliance audits and consultancy services. The findings reveal that while APIP has conducted assurance and consulting activities in accordance with professional standards, it has not fully provided adequate assurance on compliance, efficiency, and effectiveness. Moreover, its role in providing early warnings and improving governance practices remains limited.